2019
DOI: 10.1103/physrevb.99.214441
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of magnetic order and persistent spin dynamics in a quantum kagome antiferromagnet with no intersite mixing

Abstract: One of the key questions concerning frustrated lattices that has lately emerged is the role of disorder in inducing spin-liquid-like properties. In this context, the quantum kagome antiferromagnets YCu3(OH)6Cl3, which has been recently reported as the first geometrically perfect realization of the kagome lattice with negligible magnetic/non-magnetic intersite mixing and a possible quantumspin-liquid ground state, is of particular interest. However, contrary to previous conjectures, here we show clear evidence … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
50
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 60 publications
7
50
1
Order By: Relevance
“…In order to detect weak magnetic Bragg reflections, high-statistics runs were collected, with the measurement time of 60 h at each temperature. All measurements were performed on a sample from the same batch as the one used in our previous µSR investigation [35].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to detect weak magnetic Bragg reflections, high-statistics runs were collected, with the measurement time of 60 h at each temperature. All measurements were performed on a sample from the same batch as the one used in our previous µSR investigation [35].…”
Section: Methodsmentioning
confidence: 99%
“…However, more sensitive local-probe muon spin relaxation (µSR) measurements have recently disclosed static internal magnetic fields that develop in YCu 3 (OH) 6 Cl 3 below T N = 15 K [35,36]. The magnetic ordering at T N is, in fact also witnessed in an increase of the bulk magnetization below T N and in heat capacity as a broad maximum at T N [35]. However, the order appears to be rather unconventional, as it progressively sets in and is fully established over the whole sample only for T T N /3 [35].…”
Section: Introductionmentioning
confidence: 99%
“…The essential hallmark for material candidates for the presented SL scenario should be a substantial entropy s(T ) persisting well below T ≪ J. There are indeed several studies of s(T ) reported for different SL candidates (with some of them revealing transitions to LRO at very low T ), e.g., for KL systems volborthite [10], YCu 3 (OH) 6 Cl 3 [15], and recent TL systems 1T-TaS 2 [21] and Co-based SL materials [61]. Still, our model studies cannot exclude the relevant effect of additional terms, e.g., the Dzaloshinski-Moriya interaction [62,63] and/or 3D coupling, which can reduce s(T ) or even induce LRO at T → 0.…”
mentioning
confidence: 92%
“…In last two decades theoretical efforts have been boosted by the discovery of several classes of insulators with local magnetic moments [2][3][4], which do not reveal long-range order (LRO) down to lowest temperatures T . The first class are compounds, as the herbertsmithite ZnCu 3 (OH) 6 Cl 2 [5], which can be represented with Heisenberg S = 1/2 model on kagome lattice, being the subject of numerous experimental studies [6][7][8][9], now including also related materials [10][11][12][13][14][15] confirming the SL properties, at least in a wide T > 0 range. Another class are organic compounds, as κ-(ET) 2 Cu 2 (CN) 3 [16][17][18][19], where the spins reside on a triangular lattice.…”
mentioning
confidence: 99%
“…They are crucial to pinpoint the different characters and scenarios of SL behavior, in particular whether materials follow gapped or gapless SL. These quantities are mostly extracted from experiments on KL systems, the prominent example being herbertsmithite [27][28][29][30][31], but also related compounds in the same class [32][33][34][35][36][37]. Another example are organic compounds where the relevant lattice is triangular [38][39][40][41] as well as charge-density-wave system 1T-TaS 2 , recently established as SL with composite S = 1/2 spins on TL [42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%